2016
DOI: 10.1096/fj.201600263rr
|View full text |Cite
|
Sign up to set email alerts
|

Reduced adiponectin expression after high‐fat diet is associated with selective up‐regulation of ALDH1A1 and further retinoic acid receptor signaling in adipose tissue

Abstract: Adiponectin is an adipocyte-derived adipokine with potent antidiabetic, anti-inflammatory, and antiatherogenic activity. Long-term, high-fat diet results in gain of body weight, adiposity, further inflammatory-based cardiovascular diseases, and reduced adiponectin secretion. Vitamin A derivatives/retinoids are involved in several of these processes, which mainly take place in white adipose tissue (WAT). In this study, we examined adiponectin expression as a function of dietary high-fat and high–vitamin A condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 86 publications
(130 reference statements)
8
32
0
2
Order By: Relevance
“…Previous studies reported that low levels of adiponectin in serum can be a strong predictor for MetS (Kim et al 2013), insulin resistance (Awazawa et al 2011) and type 2 diabetes (Yamamoto et al 2014). Previous studies reported the reductions in adiponectin gene and protein expression under high-fat dietary condition in animals (Barnea et al 2006;Landrier et al 2017). Congruent with these past findings, our results demonstrated that the animals with MetS induced by HCHF diet had a lower level of adiponectin compared to the normal control animals.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies reported that low levels of adiponectin in serum can be a strong predictor for MetS (Kim et al 2013), insulin resistance (Awazawa et al 2011) and type 2 diabetes (Yamamoto et al 2014). Previous studies reported the reductions in adiponectin gene and protein expression under high-fat dietary condition in animals (Barnea et al 2006;Landrier et al 2017). Congruent with these past findings, our results demonstrated that the animals with MetS induced by HCHF diet had a lower level of adiponectin compared to the normal control animals.…”
Section: Discussionsupporting
confidence: 81%
“…Dietary transglutaminases can provide PPAR ligands, thus synchronising fat, and concomitantly carotenoid, uptake / availability with BCO1 up-regulation. It was described that the main BCO1-metabolite ATRA is regulating via ATRA-RAR-mediated signalling various important steps in lipid metabolism (206,225,226) , with β-Carotene bioactivation pathway a focus also on counteracting fat accumulation via energy dissipation in adipose tissue (226)(227)(228)(229) and regulation of insulin secretion (230,231) . The second possibility for negative feedback is the potential synthesis of the endogenous RXR-ligand 9CDHRA, starting from still non-identified carotenoid precursors (Rühl et al, unpublished results (160) ).…”
Section: β-Carotene Bioactivation Pathway 77mentioning
confidence: 99%
“…Adipose tissue and in particular the lipid fraction of adipocytes is an important site of carotenoid accumulation . Vitamin A is stored in adipose tissue primarily as unesterified retinol . Concentrations of carotenoids in adipose tissue have been reported by several groups (Table ).…”
Section: Further Transport and Biodistribution To Potential Target Timentioning
confidence: 99%